Virtual Joint Companies as a Means of Incentivizing SMEs to Use Occupational Health Services—A Trial in Two Municipalities in Finland From 2009 to 2011 - Ahonen, Guy; Näsman, Ove; Aboagye, Emmanuel (Frontiers in Sustainability, 2022)
Employees of Small and Medium-sized Enterprises (SMEs) can benefit from occupational health services (OHS) in the same way that employees of large organizations do. The aim of this three-year trial was to investigate whether integrating multiple SMEs into virtual joint companies may result in incentive structures like those of large companies concerning access to Occupational Health Services (OHS), which can improve wellbeing and reduce the number of sickness visits to clinics. Several SMEs were grouped together to form virtual organizations to enter into agreements with OHS providers. Two groups were created, each with a somewhat different price structure: one with a fixed annual fee and the other with a cost-dependent fee. The number of sickness visits to clinics increased among those who worked under the cost-dependent fee system, whereas it decreased among those who worked under the fixed-fee system. The findings on the work climate were inconclusive because there was no discernible difference. The improved productive time was particularly appealing to SME businesses since employees could rapidly schedule a doctor's visit and they were able to spend less time dealing with sickness-related paperwork. It also raised their awareness of their employees' health. When OHS providers could address SMEs as a group, their desire to collaborate with them improved. Furthermore, the local entrepreneur organizations, which served as the virtual headquarters for the SME groups, stated that they would be willing to continue with the work for a rather moderate compensation. The ability of SMEs to create legal organizations in the form of virtual joint companies appears to address, at least partially, the issues related to the conflict between their small sizes and Occupational Safety and Health (OSH) incentive systems to address work accidents and disease incidences. Using the proposed approach would allow for differential fee systems, as well as economic incentive systems, which presently apply predominantly to large firms, might be extended to SMEs.